Seasonal decline in leaf photosynthesis in perennial switchgrass explained by sink limitations and water deficit - Tejera-Nieves, Mauricio; Abraha, Michael; Chen, Jiquan; Hamilton, Stephen K.; Robertson, G. Philip; Walker, Berkley James (Frontiers in Plant Science, 2023)
Leaf photosynthesis of perennial grasses usually decreases markedly from early to late summer, even when the canopy remains green and environmental conditions are favorable for photosynthesis. Understanding the physiological basis of this photosynthetic decline reveals the potential for yield improvement. We tested the association of seasonal photosynthetic decline in switchgrass (Panicum virgatum L.) with water availability by comparing plants experiencing ambient rainfall with plants in a rainfall exclusion experiment in Michigan, USA. For switchgrass exposed to ambient rainfall, daily net CO2 assimilation (A_net^') declined from 0.9 mol CO2 m-2 day-1 in early summer to 0.43 mol CO2 m-2 day-1 in late summer (53% reduction; P <0.0001). Under rainfall exclusion shelters, soil water content was 73% lower and A_net^' was 12% and 26% lower in July and September, respectively, compared to those of the rainfed plants. Despite these differences, the seasonal photosynthetic decline was similar in the season-long rainfall exclusion compared to the rainfed plants; A_net^' in switchgrass under the shelters declined from 0.85 mol CO2 m-2 day-1 in early summer to 0.39 mol CO2 m-2 day-1 (54% reduction; P <0.0001) in late summer. These results suggest that while water deficit limited A_net^' late in the season, abundant late-season rainfalls were not enough to restore A_net^' in the rainfed plants to early-summer values suggesting water deficit was not the sole driver of the decline. Alongside change in photosynthesis, starch in the rhizomes increased 4-fold (P <0.0001) and stabilized when leaf photosynthesis reached constant low values. Additionally, water limitation under shelters had no negative effects on the timing of rhizome starch accumulation, and rhizome starch content increased ~6-fold. These results showed that rhizomes also affect leaf photosynthesis during the growing season. Towards the end of the growing season, when vegetative growth is completed and rhizome reserves are filled, diminishing rhizome sink activity likely explained the observed photosynthetic declines in plants under both ambient and reduced water availability.